Przelewy burzowe - kluczowe elementy sieci kanalizacyjnej miasta Głogowa = Overflow structures - key elements of sewerage network in Głogów - Nowogoński, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The character of overflow structures located in sewage system in the city Głogów was presented. Modifications initiated in system, connected with overflow structures were shown. Principles of research project enabling analysis of hydraulic conditions in overflow structures and rainfall-runoff phenomena analysis were presented.
Keywords: przelew burzowy; sieć kanalizacyjna; overflow structures; sewage systems